Isolation and expression of the Pneumocystis carinii dihydrofolate reductase gene. - Edman, J C (1989)
Pneumocystis carinii dihydrofolate reductase (DHFR; 5,6,7,8-tetrahydrofolate: NADP+ oxidoreductase, EC 1.5.1.3) cDNA sequences have been isolated by their ability to confer trimethoprim resistance to Escherichia coli. Consistent with the recent conclusion that P. carinii is a member of the Fungi, sequence analysis and chromosomal localization show that DHFR is neither physically nor genetically linked to thymidylate synthase. Expression of recombinant P. carinii DHFR in heterologous hosts provides an abundant source of the enzyme that may form a basis for the development of new therapies for this enigmatic pathogen. Studies with the recombinant enzyme show that trimethoprim is a very poor inhibitor of P. carinii DHFR and, in fact, is a more potent inhibitor of human DHFR.